(untitled) (Al-Academy, 2018)
The typographic accomplishment is the most important means of cognitive communication and carries a message from the sender to the recipient which serves a certain objective functionally, economically and advertisingly. The design of typographic accomplishment depends on two different techniques, the first is manual, which depends on the skill, training and individual achievement of the designer and his ability to design and produce typographic accomplishment with manual skill effects. The second one is the contemporary digitization which is represented by computers, programs and printers attached to them. The problem of the current research is highlighted by the following question: Does the typographic accomplishment need the manual skill of the designer and the contemporary technology? The importance of research lies in the possibility of benefiting the workers in the field of typographic design. It can be useful to the relevant government and civil offices. The aim of the research is as follows: Knowing the manual skills and modern techniques used in the typographic accomplishment and the extent of the designer’s need for them. The limits of our current research include the Spanish prints made in (2016 AD) then the specific terms related to the subject under study are determined, namely (skill, technology). The theoretical framework and the previous studies: the theoretical framework included two sections: the manual skill and its use in typographic design, the contemporary typographic techniques, and then the most important indicators that resulted from the theoretical framework were also listed. In the research procedures, the researcher relied on the descriptive method (the method of content analysis) in the analysis of the models of research by (3) models. The researcher came up with a number of results, including: The manual skill and its use of different means, tools and materials is employed despite the great progress achieved in contemporary technology in the field of design and printing. The research also came up with a set of conclusions, such as: The typographic accomplishment carries the specifications, method and idea of ​​the designer and explains them. Then the researcher put forward a set of recommendations including: asserting the role of manual skill in the completion of printing designs through paying attention to the syllabi in the specialized lessons of the scientific departments in the colleges and technical institutes